공군사관생도의 G-test 결과에 따른 피로도, 국방체력 및 신체조성의 관련성 - 김인기; 정덕화; 성준영; 김근수 (Exercise science (Seoul, Korea), 2022)
PURPOSE: This study aimed to analyze the G-test results based on body composition and heart rate of fourth grade Air Force cadets, identify the relationships among body composition, heart rate, and G-resistance, and provide basic data for pilots and Air Force cadets to strengthen the G-tolerance. METHODS: This study used wearable devices to measure the heart rate and fatigue of 27 fourth-grade cadets of the Air Force Academy. Physical composition and physical fitness were assessed. Based on the measurement results, G-test result analysis and correlation analysis were performed. RESULTS: G-test results showed a steady heart rate (p=.015), deep sleep time (p<.001), and fatigue (p=.008) which have significant differences. Further, a 10-second heart rate at G-test (p<.001) and maximum heart rate (p<.001). There was also a statistically significant difference. CONCLUSIONS: Effective G-test success for Air Force cadets would require improving aerobic performance, continuous fatigue, and physical fitness management. If various variables that affect G-test are analyzed and applied to physical education and physical training through continuous research over the next 2–3 years, it is expected to have a better outcome on the G-test success for every cadet. KCI Citation Count: 0